Avaliação da qualidade dos serviços da Estratégia Saúde da Família dos municípios da região de saúde Baixada Cuiabana - Mato Grosso - Oliveira, Lays Andrade de (2019)
The institution of a care model committed to the principles of the Brazilian Unified Health System led to the creation of the Family Health Strategy (ESF) to reorient the organization of Primary Health Care (PHC). The evaluation of quality in Primary Care has been institutionalized in Brazil through the National Program for Improvement in Access and Quality of Primary Care (PMAQ) in 2011, with the purpose of improving quality and incorporating evaluative practices in health services. The PMAQ is organized in three phases - adhesion and contracting, certification and re-contractualization - and a strategic transversal axis of development, composed of self-assessment. The research focuses exclusively on the data resulting from the self-assessment carried out by the respective teams, understanding it as a strategic point for improving the quality of health care, for facilitating the reflection of the organization of the work process and for the effectiveness of the evaluative practice in the context of APS. The objective of this study was to evaluate the quality of the Family Health Strategy teams of the municipalities of the Baixada Cuiabana Health Region, Mato Grosso, based on the results of the self-assessment of the instrument Assessment of Improvement of Access and Quality (AMAQ). This is an evaluative cross-sectional survey with a quantitative approach, developed in ten municipalities of the Baixada Cuiabana Health Region, which is the setting for the capital of the state of Mato Grosso. Data from the AMAQ instrument, used in the PMAQ self-assessment the process were used. The study population comprises the ESF teams of the municipalities that joined the 3rd cycle of the PMAQ in 2017. The data were collected on the e-Manager site and/or on-site and analyzed using the 14 subdimensions that makeup part I - Basic Attention - of the AMAQ. For the description and analysis of the score attributed to the questions, the absolute score of the quality standards for each municipality and the ESF team was used in the study, based on the quality standards adopted in the AMAQ. The results reveal the fragility of the quality of the ESF teams, especially in the area of Management. On the other hand, the Permanent Education, Work Process and Integral Attention to Health dimension reached the expected quality standard in the ten municipalities, however, it still presents important challenges, especially with regard to the permanent education and qualification of Attention teams Basic. Regarding the comparison of the quality differentials of the FHT teams, among small and large municipalities, there was little influence of this variable on quality standards. However, by comparing the results of the self- assessment with those of the certification, it was possible to identify that the teams did not achieve significant quality changes between self-assessment and certification. Self-evaluation is a strategy of change of practice, with the potential to improve the quality of services, work processes and health actions, however, it is necessary to engage all the actors in their process. It should not be treated, as a bureaucratic method, but as a potential tool for evaluation and qualification and for PHC in Brazil.